2018
DOI: 10.1002/elan.201800395
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Sensing by a Green Modified Molecularly Imprinted Poly L‐Lysine/Sodium Alginate‐activated Carbon/Glassy Carbon Electrode Based on Computational Design

Abstract: A different molecularly imprinted composite film with the exploit of computational design is synthesized. The proposed composite is used for electrode modification to determine morphine. The ratio of monomer to template in optimum condition was obtained 4. The modification of the electrode was achieved by electropolymerizing L‐lysine in the presence of morphine on the surface of sodium alginate and activated carbon (SA‐AC) on glassy carbon electrode (GCE). The SA‐AC composite with special surface area suits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Salajegheh et al [79] have reported an interesting concept of using BAC derived from walnut shells (with chemical activation using HNO 3 ) to prepare a molecularly imprinted L-lysine(MIPL)/sodium alginate (SA)/BAC/GCE for the determination of morphine, as depicted in the schematic diagram in Figure 3.…”
Section: Figure 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Salajegheh et al [79] have reported an interesting concept of using BAC derived from walnut shells (with chemical activation using HNO 3 ) to prepare a molecularly imprinted L-lysine(MIPL)/sodium alginate (SA)/BAC/GCE for the determination of morphine, as depicted in the schematic diagram in Figure 3.…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…Salajegheh et al [79] . have reported an interesting concept of using BAC derived from walnut shells (with chemical activation using HNO 3 ) to prepare a molecularly imprinted…”
Section: Introductionmentioning
confidence: 99%
“…So far, di erent analytical methods have been utilized for the detection of PC; chemiluminescence [4], high-performance liquid chromatography [5], mass spectrometry [6], spectrophotometry [7], and electrochemical sensors have been used [8]. Most of the techniques are di cult, time-consuming processes, and they generally demand professional apparatus, except for electrochemical sensors [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Using computers as research tools allows performing a large number of calculations and simulations in order to select the most suitable structure and composition of functional monomer, template, crosslinker, and porogen/solvent [ 21 ]. The core of such calculations is based on input data related to the chemical composition, the structure at the atomic scale, the distribution of electronic charges leading to dipole formation as well as weak, long range dispersion interactions governed by hydrophobic van der Waals forces [ 22 ]. All these factors contribute to a direct picture of a molecular association and the corresponding interaction energy.…”
Section: Introductionmentioning
confidence: 99%